REGRESSION OF LIVER FIBROSIS IN SCHISTOSOMA MANSONI INFECTED SUDANESE SUBJECTS AFTER PRAZIQUANTEL TREATMENT - Rahoud, Siddig A.; Mergani, Adil Mergani; Khamis, Ammar H. Khamis; Saeed, Osman K. Saeed; Mohamed-Ali, Qurashi; Dessein, Alain J.; A. Elwali, Nasr Eldin M. A. Elwali (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 2 (2005), 2005)
Objectives : 1-To evaluate the effect of Praziquantel (PZQ) therapy on the regression of liver fibrosis in an endemic population. 2-To determine the factors controlling the regression of hepatic fibrosis (e.g. gender, age and grade of fibrosis).   Material and methods: An association study of a cohort of one hundred seventy seven Sudanese patients infected with Schistosoma mansoni (82 males 46%, 95 females 54%) was conducted to evaluate the factors controlling the regression of liver fibrosis 39 months after treatment with PZQ using ultrasound evaluation. SPSS (Statistical Package for Social Science) software was used for statistical analysis. Chi- Square was used to compare the two phenotypes (regression and progression) in the study subjects. Results : PPF was regressed in 63 patients (36%) from higher grades of fibrosis to lower ones. While in 24 patients (13 %) the disease progressed to higher grades. In addition, the grade of PPF did not change in 90 patients (51%).  The mean values of portal vein diameter (PVD), splenic vein diameter (SVD), and index liver size (ILS) in subjects in whom PPF regressed after treatment were significantly lower than in subjects in whom the disease was progressed (P < .0001, P = .031, and P = .003 respectively).The progression of hepatic fibrosis in males (n = 15, 18 %) was greater than that of females (n = 9, 9 %). Patients who showed regression of PPF or progression of the disease tend to cluster in certain families.